Editorial-The sweet sixteen special! - Shrestha, Bikash (Medical Journal of Shree Birendra Hospital, 2017)
Sixteen years! Our own Medical Journal of Shree Birendra Hospital is in the middle of charming teen years now. Yes, it is definitely sweet sixteen! And yes, it has definitely come a long way since its inception and we must congratulate ourselves and feel proud that we are here, and with more zeal to improve and learn. I would like to thank all our readers, authors, reviewers as well as editors and mentors of NepJol for their continuous support and love which has kept the journal alive and kicking for so many years!First of all, we are happy to share some news. We have recently updated our journal guidelines for authors. We have tried to simplify the whole process of submission. We hope that the simpler guidelines will make the authors more comfortable to submit their articles online. We have also been successful in adding many prominent national and international editors to our editorial board. We have added Dr Samir Lamichhane from Maharajgunj Medical Campus, Institute of Medicine, Tribhuvan University, Kathmandu, Nepal (Department of Pharmacology), Dr Manisha Bajracharya from KIST Medical College and Teaching Hospital, Imadole, Lalitpur (Department of Obstetrics and Gynaecology), Dr. Barsha Bajracharya from Shree Birendra Hospital, NAIHS, Kathmandu, Nepal (Department of Dental Surgery) as our Editorial Board members. We must consider ourselves very privileged that some reputed academicians have joined our team as international editors. We are extremely honored to have Prof. Dr. Babill Stray-Pederson, University of Oslo, Norway (Department of Obstetrics and Gynaecology), Prof. Dr. Deepak Batura from London North West Healthcare NHS, London, UK (Department of Urosurgery), Dr. Dipendra Raj Pandeya from Al Jouf University, Saudi Arabia (Department of Clinical Biochemistry), Dr. Santosh Pandit from Chalmers University of Technology, Sweden (Department of Biology and Biological Engineering) and Dr. Usman Mahboob from Khyber Medical University, Pakistan (Institute of Health Professions Education And Research) as international editors in our team. We are very excited to have such distinguished mentors as our team members. Thank you and welcome to all.With the vigor and enthusiasm of additional editors, we have set some goals for our journal. First and foremost, a journal has to be punctual. We need to maintain the punctuality of our journal. Presently, we have been lagging behind in publication of issues. With two consecutive future publications, we aim to publish further issues on specified time biannually (Jan and July).Secondly, with the guidance and support of additional editors, we hope that our journal would flourish more in the national as well as international field. For this, we expect that we shall be able to involve all the editorial board members in the journal equally and effectively. We are certain that their invaluable contribution would be vital for the progress of our journal. Thirdly, we have initiated steps towards indexing and hope that we shall soon get indexed into reputed indexing services. With better indexing, we believe that the overall scope of our journal will widen and we shall have broader and discerning audience. Fourthly, we aim to collaborate with different organizations and conduct regular training sessions for our authors in scientific manuscript writing. We firmly believe that training is imperative for the authors to improve their writing skills. With better quality of authors, needless to reiterate, we will get better articles and our journal would be at par with any other well-known medical journal that we look up to. But whatever we bring out, without feedback, we-the editorial team-too will not learn, nor grow. I would like to conclude by requesting all our readers, authors, reviewers, editors, as well as mentors to give us feedback and comments, so that we can strive continuously for betterment. Lastly, I would like to congratulate and express our gratitude to the editors who have come on board. Welcome and thank you all once again.